Matching sistem penganggaran dengan strategi bisnis dan kompleksitas tugas serta implikasinya terhadap kinerja manajerial - Alim, Mohammad Nizarul (Akutansi Bisnis & Manajemen ( ABM ), 2006)
The Im of Study of investigate impact of budgeting system effectivity and it's matching with business Strategy and job complexity on managerial performance budgeting system definite as a comprehensive set of budgeting komponen including budget participation, goldiful di, budget evaluatif style, and feedback titik one hundred and nine Manager of strategi bisnis study. Empirical devidence that matching between budgeting system with business Strategy and job complete City have positive signification on managerial performance titik-titik sistem titik the findings of this research gift important contribution and extension for badgeting theory and practice.